Atypical exanthems. - Gelmetti, C. (European Journal of Pediatric Dermatology, 2018)
In this article, the Author first analyzes typical exanthems and their classification with the scope of a better understanding of atypical exanthems. He then discusses atypical exanthems including the asymmetrical periflexural exanthem of childhood, the Gianotti-Crosti syndrome, the Kawasaki disease, and the drug exanthems. He also analyzes both the diagnostic criteria for atypical exanthems and the differential diagnosis between infectious exanthems and drug exanthems.